1995
DOI: 10.1210/jcem.80.1.7829645
|View full text |Cite
|
Sign up to set email alerts
|

Marked hypocholesterolemia in a case with adrenal adenoma--enhanced catabolism of low density lipoprotein (LDL) via the LDL receptors of tumor cells.

Abstract: A 16-yr-old girl was hospitalized because of amenorrhea and virilism, and was diagnosed with an adrenal tumor on the right side. Her serum androgen levels were markedly elevated, and severe hypocholesterolemia (total cholesterol, 0.59 mmol/L) was observed. After resection of the tumor, her serum cholesterol level dramatically rose to normal, suggesting a role of this tumor in her marked hypocholesterolemia. To investigate the mechanism of hypocholesterolemia in this case, we examined the effects of dehydroepia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…Both human LDL-and HDL-C were used for steroid production by primary adrenocortical cells obtained from adenomas [238]. These findings were also found in adrenocortical carcinoma cells, mainly by the action of LDLR and SR-BI [239,240]. In the latter report, the tumor tissue of the female patient expressed high levels of LDLR and a severe reduction in LDL-C and HDL-C. More importantly, her serum cholesterol levels were normalized few days after tumor removal [240].…”
Section: Adrenal and Testicular Cancermentioning
confidence: 85%
“…Both human LDL-and HDL-C were used for steroid production by primary adrenocortical cells obtained from adenomas [238]. These findings were also found in adrenocortical carcinoma cells, mainly by the action of LDLR and SR-BI [239,240]. In the latter report, the tumor tissue of the female patient expressed high levels of LDLR and a severe reduction in LDL-C and HDL-C. More importantly, her serum cholesterol levels were normalized few days after tumor removal [240].…”
Section: Adrenal and Testicular Cancermentioning
confidence: 85%
“…In vitro and in vivo studies demonstrate that LDL-C is increasingly associated with carcinogenesis. This has been attributed to an increase in LDL-C uptake and receptor activity [46][47][48][49][50][51][52]. Additionally, oxidative stress can induce carcinogenesis and oxidation of low-density lipoprotein.…”
mentioning
confidence: 99%
“…It is reported that these LDL receptors are overexpressed on different types of solid tumors like colon cancer [ 11 ], prostate tumors [ 12 ], adrenal tumors [ 13 ], hormone unresponsive breast tumors [ 14 ], cancers of gynecological origin [ 15 ], malignant brain tumors [ 16 ], lung tumor tissues [ 17 ], and leukemia [ 18 21 ]. The reason might be that in a pathological condition like solid tumor growth, the rapidly dividing cells require high cholesterol content and therefore, LDL receptors are overexpressed so that plasma-derived LDL could mobilize the cholesterol for the rapidly dividing cancer cells.…”
Section: Introductionmentioning
confidence: 99%